Special Auxiliary Exercises And Their Effect On Learning The Accuracy Of The Straight Ground Tennis Service For Junior Players - Ismael, Maher Mohammed; Abdulghafoor, Suha Darweesh (International Journal of Psychosocial Rehabilitation, 2020)
Modern science has a goal to reach the best technical performance through the use of special auxiliary exercises and their effect on learning in the accuracy of the straight-ground tennis transmission. The game of tennis takes perfection for the first performance, starting with the physical exercises that prepare the body as a whole, as well as focusing on the working muscle groups that will perform during the game and which ultimately leads to the control of the technique and the correctness of performance, so the research adopted tennis exercises for the straight and ground service of the emerging players, thus the goal Research to know the impact of exercises to help learning the accuracy of the transmitter straight ground tennis. The researcher made the assumption (the presence of significant differences between the pre and post test and in favor of the post test) and after identifying the fields of research, the researcher dealt with the third chapter, which occupies the research methodology and its field procedures, so the research sample was composed of 10 players representing the Federation Center in Tennis- the International People’s Stadium and was approved in the technical performance test (Technique) for the skill of the accuracy of the straight ground transmission on the apparent form of the skill through its three sections (preparatory, main, and final), as three consecutive attempts were given to each player to perform this skill and these attempts were evaluated by two specialized evaluators and the evaluation score of technical performance was ( 10 marks) and the best attempt was counted from the three attempts for each index. While the researcher adopted in assessing the accuracy level of the transmitter for the skill of the straight ground transmitter, which measures the level of accuracy of the straight transmitter in tennis, after that the researcher used a set of statistical means. Then the research hypotheses were answered through Chapter Four, and it was found that there are significant differences between the pre and post tests in the level of technical and skill performance in the accuracy of the straight transmission in tennis and in favor of the post test. The results also showed that the performance of the straight line accuracy level was more advanced than the pre-test of the same test.